2009
DOI: 10.1017/s1368980009004947
|View full text |Cite
|
Sign up to set email alerts
|

The relative importance of social class and maternal education for breast-feeding initiation

Abstract: Objective: To examine changes in breast-feeding take-up rates among young children in Scotland and to assess whether maternal education or occupationbased social class is a stronger and better predictor of breast-feeding take-up. Design: Binary logistic regression models were developed from the first sweep of the Growing Up in Scotland longitudinal survey, for the two cohorts of children. Results: Mothers from more privileged social classes and those with more educational qualifications resulted as more likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 20 publications
6
35
2
1
Order By: Relevance
“…Skafida etal acknowledges the importance of maternal education on breastfeeding and found that higher educational qualifications are associated with an increased rate of breast feeding take up [7].…”
Section: Discussionmentioning
confidence: 99%
“…Skafida etal acknowledges the importance of maternal education on breastfeeding and found that higher educational qualifications are associated with an increased rate of breast feeding take up [7].…”
Section: Discussionmentioning
confidence: 99%
“…Os lactentes cujas mães possuíam emprego fora de casa apresentaram maior frequência de consumo de vegetais e leguminosas. Com exceção do feijão, o maior nível de escolaridade foi associado ao menor consumo de alimentos considerados impró-prios para essa faixa etária, pois essas mulheres possivelmente têm maior acesso às informações sobre práticas alimentares saudáveis 31 . Esse aspecto pode ser observado no trabalho realizado por Corrêa et al 32 , na cidade de Florianópolis (SC), em que as mães com menos de oito anos de estudo apresentaram o dobro de chance de oferecerem alimentos do grupo dos doces (açúcar de adição, bolachas, pudins e gelatinas) para os filhos.…”
Section: I S C U S S ã Ounclassified
“…Eating patterns and behaviours in infants and young children are influenced by complex interrelated factors such as cultural beliefs (1) , parental or child interactions and feeding styles (2)(3)(4)(5) , as well as the parent's or primary caregiver's education, experiences, attitudes and social and economic circumstances (6)(7)(8) .…”
mentioning
confidence: 99%